Production of Biosurfactants By Arthrobacter Sp . N3 , a Hydrocarbon Degrading Bacterium (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Different screening methods, such as emulsification capacity and oil spreading assays, hydrocarbon overlay agar and modified drop collapse methods were used to detect biosurfactant production by hydrocarbon degrading Arthrobacter sp N3 strain. It was indicated that oil spreading assay was the most reliable method to detect biosurfactant production. To investigate biosurfactant production, batch cultivation of Arthrobacter sp N3 was carried out in a fermenter with complex nutrient medium supplemented by sunflower oil as a carbon source. The highest oil displacement activity was achieved when Arthrobacter sp N3 strain was cultivated in two stages (with aeration for cell production and without aeration for biosurfactant synthesis). Then, two forms of the biosurfactant (crude preparation and partially purified biosurfactant) were recovered from the culture liquid. Furthermore, the biosurfactant produced by Arthrobacter sp N3 strain was analyzed by thin layer chromatography and it was estimated that even a few compounds have surface activity. The effect of temperature and pH on biosurfactant activity was also studied. It was observed that no appreciable changes in biosurfactant activity occurred at temperature and pH values ranges of 4–125 ºC and 5–10, respectively.